The Role of Fibroblast Growth Factors in Tooth Development and Incisor Renewal - Du, Wen (Stem Cells Int, 2018)
The mineralized tissue of the tooth is composed of enamel, dentin, cementum, and alveolar bone; enamel is a calcified tissue with no living cells that originates from oral ectoderm, while the three other tissues derive from the cranial neural crest. The fibroblast growth factors (FGFs) are critical during the tooth development. Accumulating evidence has shown that the formation of dental tissues, that is, enamel, dentin, and supporting alveolar bone, as well as the development and homeostasis of the stem cells in the continuously growing mouse incisor is mediated by multiple FGF family members. This review discusses the role of FGF signaling in these mineralized tissues, trying to separate its different functions and highlighting the crosstalk between FGFs and other signaling pathways.